2003
DOI: 10.1002/arch.10080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silkworm paralytic peptide on in vitro hematopoiesis and plasmatocyte spreading

Abstract: Bombyx mori paralytic peptide (BmPP), a multifunctional cytokine-like molecule, is expressed in the hematopoietic organ-wing imaginal disc complex, suggesting that BmPP is involved in both immune response and the hematopoietic process. We studied the effects of BmPP on plasmatocytes and hematopoietic organs of the silkworm. BmPP (1 microM) stimulated spreading of circulating plasmatocytes, but the percentage of spread plasmatocytes was only 20%. Over 10 nM of BmPP, however, elicited prominent spreading in 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…The most potent known activator of plasmatocytes is the plasmatocyte-spreading peptide (PSP) (Clark et al, 1997), homologs of which have been identified from a number of other moth species, including M. sexta (Clark et al, 2004). PSP and related homologs are the only molecules identified to date that activate plasmatocytes (Clark et al, 1997;Strand et al, 2000;Miura et al, 2002;Nakahara et al, 2003), although circumstantial evidence suggests that several other molecules besides PSP mediate plasmatocyte function (Lackie, 1988;Gillespie et al, 1997;Lavine and Strand, 2002). However, there has been no detailed investigation of the participation and role of PSP in hemocytic reactions responsible for bacterial clearance in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The most potent known activator of plasmatocytes is the plasmatocyte-spreading peptide (PSP) (Clark et al, 1997), homologs of which have been identified from a number of other moth species, including M. sexta (Clark et al, 2004). PSP and related homologs are the only molecules identified to date that activate plasmatocytes (Clark et al, 1997;Strand et al, 2000;Miura et al, 2002;Nakahara et al, 2003), although circumstantial evidence suggests that several other molecules besides PSP mediate plasmatocyte function (Lackie, 1988;Gillespie et al, 1997;Lavine and Strand, 2002). However, there has been no detailed investigation of the participation and role of PSP in hemocytic reactions responsible for bacterial clearance in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Among insects, apart from Drosophila, hematopoiesis has been primarily studied in Orthoptera (Hoffmann et al, 1974;Hoffmann and Porte, 1973;Hoffmann, 1970) and Lepidoptera (Nakahara et al, 2010(Nakahara et al, , 2006(Nakahara et al, , 2003Nardi et al, 2003).Two extracellular peptides have been identified in Bombyx mori that have some impact on hematopoiesis. The paralytic peptide BmPP (NP_001036883.1), showing inhibitory activity, whereas the insulin-like peptide Bombyxin (BAA00246.1) stimulates the proliferation of hematopoietic cells (Nakahara et al, 2006(Nakahara et al, , 2003.…”
Section: Drosophilamentioning
confidence: 99%
“…The paralytic peptide BmPP (NP_001036883.1), showing inhibitory activity, whereas the insulin-like peptide Bombyxin (BAA00246.1) stimulates the proliferation of hematopoietic cells (Nakahara et al, 2006(Nakahara et al, , 2003. None of these peptides were detected in the P. leniusculus transcriptome, again showing differences between species in extracellular hematopoietic growth factors and cytokines.…”
Section: Drosophilamentioning
confidence: 99%
“…A cytokine-like molecule (coelomic cytolytic factor) found in the earthworm, Eisenia foetida, with lectinlike activities similar to TNF instead suggests a convergent evolution of cytokines (9). Similarly, the ENF peptides found in some lepidopteran insects have cytokine-like activity, but they lack any sequence homology to vertebrate proteins (10,11).…”
mentioning
confidence: 99%